The Improvement of Management Model Learning Islamic Education (PAI) Based on Scientific Approach - Muntari, Witi Muntari; Slamet, Achmad; Subagyo, Subagyo (Educational Management, 2018)
Muntari, Witi, 2018. Development of PAI Learning Model Management Based on Scientific Approach ". Thesis. Graduate Program Management Education Study Program. Semarang State University. Supervisor I Prof. Dr. H. Achmad Slamet, M.Si, Advisor II Dr. Subagyo, M.Pd. Keywords: Development of Learning Models, Scientific Approaches, PAI Learning. This research begins with anxiety about the learning process in schools that use conventional and teacher-centered models, which affect the achievement of student learning outcomes. With the 2013 curriculum it is clear that the learning process must be more active with a scientific approach and learner-centered. This is what then makes the author conduct research at the Semarang 01 PGRI Vocational School to find out the PAI learning process with a scientific approach. This study aims to analyze; (1) Management of the factual model of PAI learning, (2) Management of hypothetical models of PAI learning model management with scientific approaches, (3) Finding appropriate PAI learning model management with a scientific approach. This research was designed in the form of Research and development (R & D). Data collection methods used are observation, interview, and documentation. While to analyze the data used an analysis with a phenomenological approach that departs from specific facts or phenomena that occur in the field and then drawn conclusions. The results show that: (1) the learning process still uses conventional learning models and is teacher-centered. (2) development of learning models based on scientific approaches. (3) an appropriate learning model is right to be used as a PAI learning model based on a scientific approach.